2015
DOI: 10.3109/0142159x.2015.1017448
|View full text |Cite
|
Sign up to set email alerts
|

Feedback-giving behaviour in performance evaluations during clinical clerkships

Abstract: Teachers' feedback-giving behaviour within the clinical context results from the interaction between personal, interpersonal and contextual factors. Increasing insight into how teachers use mini-CEX instruments in daily practice may offer strategies for creating a professional learning culture in which feedback giving and seeking would be enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 25 publications
1
65
0
3
Order By: Relevance
“…To our knowledge, this study is the first one about specific student perception on meaningful feedback when performing an EPA. Our results are consistent with the general literature about feedback [17, 25, 3032]. However, related to the preparation for the execution of an EPA, specific aspects of feedback turned out to be essential as highlighted by our participants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, this study is the first one about specific student perception on meaningful feedback when performing an EPA. Our results are consistent with the general literature about feedback [17, 25, 3032]. However, related to the preparation for the execution of an EPA, specific aspects of feedback turned out to be essential as highlighted by our participants.…”
Section: Discussionsupporting
confidence: 91%
“…The difficulty may be caused by the fact that the clinical setting is unpredictable, and different supervisors observe different performances of the same students differently [7, 15, 16]. Supervisors vary in how they observe and integrate these observations into feedback, especially when the observation is part of an assessment procedure [17, 18]. As a result, the way feedback is tailored to individual students varies.…”
Section: Introductionmentioning
confidence: 99%
“…Students need to be trusted in order to be given opportunities to participate and therefore learn, and must participate in order to be trusted, as discussed by Hauer and others (2014). Bok and others (2016) found that supervisors gave more clinical responsibilities to highly engaged veterinary students. Thus, engagement and trustworthiness are interdependent, an idea supported by the findings of this research, in which positive engagement was usually associated with positive trustworthiness and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Observação direta pelo avaliador, geralmente professor, foi um fator relatado: 35 , em que discentes associam a observação do seu desempenho como fonte de informação para o observador dar devolutivas, relacionando diretamente a quantidade de atividades sob observação com a frequência do feedback.…”
Section: Fatores Facilitadores Relacionados à Ocorrência Do Feedbackunclassified
“…Bok et al 35 e Ramani 11 descreveram que o estabelecimento de uma relação de confiança entre aluno e professor em estágio clínico longitudinal é fator importante para criar um ambiente de aprendizagem propício ao feedback efetivo de intercâmbio bilateral.…”
Section: Características Positivas Do Docente Para Dar Feedbackunclassified